Interactions Between Allogeneic Mesenchymal Stromal Cells and the Recipient Immune System: A Comparative Review With Relevance to Equine Outcomes - Kamm, J. Lacy; Riley, Christopher B.; Parlane, Natalie; Gee, Erica K; McIlwraith, C. Wayne (Frontiers in Veterinary Science, 2021)
Despite significant immunosuppressive activity, allogeneic mesenchymal stromal cells (MSCs) carry an inherent risk of immune rejection when transferred into a recipient. In naïve recipients, this immune response is initially driven by the innate immune system, an immediate reaction to the foreign cells, and later, the adaptive immune system, a delayed response that causes cell death due to recognition of specific foreign cell antigens by host cells and antibodies. This review describes the actions of MSCs to both suppress and activate the different arms of the immune system. We then review the survival and effectiveness of the currently used allogeneic MSC treatments.